Relationship between Environmental Quality, Hygiene, Food Sanitation, and Food Handling Factors with Escherichia coli Germ Rates at Snack Food Centers in Jambi City - Hadiyati, Titi; Suryono, Suryono; Guspianto, Guspianto (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background : Food safety is a public need, safe food will protect and prevent disease and health problems. Environment and food need attention if you want to live healthy and get enough nutrition. Hygiene sanitation is an effort to control the factors of people, places, equipment and food. In producing ready-to-eat food that is safe and healthy, the principles of sanitation hygiene must be implemented. Food handlers are people who have direct contact with food. The purpose of this study was to analyze the relationship between environmental quality, sanitation hygiene, handler behavior and knowledge of food handlers with the number of Escherichia coli bacteria. Method : The research design is a quantitative method using laboratory analysis with a cross sectional research design. Results : Research shows that there is a significant relationship between environmental quality, food sanitation hygiene, food handling behavior and knowledge of food handlers with the number of Escherichia coli germs in the Jajanan Food Center, Jambi City. Conclusion : There is a significant relationship between environmental quality, food sanitation hygiene, food handling behavior and knowledge of food handlers with the number of Escherichia coli bacteria.